Review paperThe basics of intravascular optical coherence tomography - Roleder, Tomasz; Jąkała, Jacek; L. Kałuża, Grzegorz; Partyka, Łukasz; Proniewska, Klaudia; Pociask, Elżbieta; Zasada, Wojciech; Wojakowski, Wojciech; Gąsior, Zbigniew; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Optical coherence tomography (OCT) has opened new horizons for intravascular coronary imaging. It utilizes near-infrared light to provide a microscopic insight into the pathology of coronary arteries in vivo . Optical coherence tomography is also capable of identifying the chemical composition of atherosclerotic plaques and detecting traits of their vulnerability. At present it is the only tool to measure the thickness of the fibrous cap covering the lipid core of the atheroma, and thus it is an exceptional modality to detect plaques that are prone to rupture (thin fibrous cap atheromas). Moreover, it facilitates distinguishing between plaque rupture and plaque erosion as a cause of acute intracoronary thrombosis. Optical coherence tomography is applied to guide angioplasties of coronary lesions and to assess outcomes of percutaneous coronary interventions broadly. It identifies stent malapposition, dissections, and thrombosis with unprecedented precision. Furthermore, OCT helps to monitor vessel healing after stenting. It evaluates the coverage of stent struts by the neointima and detects in-stent neoatherosclerosis. With so much potential, new studies are warranted to determine OCT’s clinical impact. The following review presents the technical background, basics of OCT image interpretation, and practical tips for adequate OCT imaging, and outlines its established and potential clinical application.